Analysis of Arabic Morphology Questions for Students of Arabic Language Education Program - Mubaligh, Ahmad (Abjadia : International Journal of Education, 2023)
The study in this research is aimed at explaining information about the quality of the questions used in mid-semester exams in courses for students of the Arabic Language Education Study Program. This research uses quantitative descriptive research, where data was obtained through documentation techniques. The research results showed that all the question items were declared valid. However, the level of Validity was still in the medium category with nine questions (36%) and the low category with 16 questions (64%). The level of reliability was in the high category (0.786), the level of difficulty of the questions was not balanced, there are four questions (16%) items in the difficult category, 19 questions (76%) in the medium category, and two questions (0.8%) in the easy category, and the level of ability is different, all the items differ in the ability of students in the upper group and lower group